Results Study Different Varieties and Agrotechniqs of Buchwheat (Fagopyrum esculentum Moench) - Ganbaatar, Munkhjin; Ochirbat, Munkhjargal (International Journal For Research In Agricultural And Food Science, 2021)
Buckwheat is one of the most important traditional pseudocereals and a multipurpose crop, belonging to genus Fagopirum of the family Polygonaceae. Buckwheat grain grown mainly for human consumption and as animal feed, although it can also be used as a vegetable, a green manure crop, as a smother crop to crowd out weeds and as a source of buckwheat honey. Common buckwheat (Fagopyrum esculentum Moench) has been a crop of secondary importance in many countries and it has persisted through centuries of civilization and enters into the agriculture of nearly every country where cereals are cultivated. The objective of the research was to establish optimal agrotechnology including, possible varieties, vegetation period, planting space and seed quality in cultivating Fagopyrum esculentum Moench in Central cropping region of Mongolia. The results showed the chosen varieties matured around 88 to 108 days of planting and the harvest weighed 5.8-11.3 centner per hectare. Among them, the russian variety, Zyemlyachka, planted 15th May, provided the greatest yield at 1.8-3.2 centner per hectare. Furthermore, planting the said cultivar at a distance of 30cm between rows, resulted in higher yield (1.30-3.91 centner per hectare) than other alternatives. All of the chosen varieties in the study yielded high quality seeds, good grain evenness and less hulled seeds.